Shame and social work : theory, reflexivity and practice - Frost, Liz, 1953-; Magyar-Haas, Veronika; Schoneville, Holger; Sicora, Alessandro (Policy Press, 2020)
Examining experiences of shame and stigma in the context of austerity and the declining welfare state, this book shows how social work can ameliorate the impacts of shame through sensitive, reflective and relationship-based practice. It provides a broad understanding of shame and looks at its impact on both service users and practitioners.